2013
DOI: 10.4066/amj.2013.1675
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of unused, disposable non-sterile gloves on a hospital orthopaedic ward

Abstract: Health care workers introduced skin commensals and pathogenic bacteria into glove boxes indicating that unused, non-sterile gloves are potential pathogen transmission vehicles in hospitals. Findings highlight adherence to handwashing guidelines, common glove retrieval practice, and glove-box design as targets for decreasing bacteria transmission via gloves on hospital wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
1
19
2
2
Order By: Relevance
“…An early study showed that gloves in boxes were not subject to significant contamination throughout duration of box use, regardless of the duration of time that the boxes were open. 152 However, researchers in an orthopedic ward in New Zealand found contamination of 13.2% of unused nonsterile gloves with potential pathogens, albeit in low numbers, 153 suggesting that hand hygiene before reaching for gloves or a different design for glove boxes may be important. 3.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…An early study showed that gloves in boxes were not subject to significant contamination throughout duration of box use, regardless of the duration of time that the boxes were open. 152 However, researchers in an orthopedic ward in New Zealand found contamination of 13.2% of unused nonsterile gloves with potential pathogens, albeit in low numbers, 153 suggesting that hand hygiene before reaching for gloves or a different design for glove boxes may be important. 3.…”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…gloves, in open glove boxes on a hospital orthopaedic ward, were contaminated by contact with unclean healthcare worker hands. 6 Significantly more skin commensals and pathogenic bacteria, including Staphylococcus aureus in 13% of samples, were recovered from boxes 3, 6 and 9 days after opening the boxes than from samples obtained immediately after opening glove boxes.…”
Section: Introductionmentioning
confidence: 94%
“…Jennifer R Amos*, Ashley S Moy*, Audrey Gomez Department of Bioengineering, University of Illinois at Urbana-Champaign *equal contribution clinical setting therefore increases the potential for pathogen transmission and the subsequent risk of nosocomial infection. 2 The risk of pathogen transmission via unused, nonsterile gloves in a hospital setting has recently been demonstrated by Hughes et al, 2 who showed that unused gloves on a hospital orthopaedic ward were contaminated prior to use -likely by contact with unclean healthcare worker hands. Our aim was therefore to minimise the potential for pathogen transmission by creating a touch-free glovedispensing system that minimises exposure of the gloves in the box to air and to user handling.…”
Section: Design Of a New Non-sterile Glove-dispensing Unit To Reduce mentioning
confidence: 99%